Interplay between host genetics and gut microbiome composition in the Japanese population - Ortega-Reyes, David; Takeuchi, Tadashi; Ogata, Yusuke; Iwami, Takuro; Suda, Wataru; Kubota, Tetsuya; Kubota, Naoto; Kadowaki, Takashi; Tomizuka, Kohei; Ohno, Hiroshi; Horikoshi, Momoko; Terao, Chikashi (Frontiers in Microbiomes, 2025)
BackgroundHost genetics significantly influence the composition of the gut microbiota, but this relationship remains poorly understood, especially in non-European populations. This study aims to investigate the associations between host genetic variation and gut microbiome composition in the Japanese population and to assess methodological factors affecting reproducibility in microbiome research.MethodsWe performed whole-genome sequencing on 306 Japanese individuals and obtained their gut microbiome profiles using shotgun metagenomic sequencing. Genome-wide association studies (GWAS) were conducted to identify associations between host genetic variants and the relative abundance of microbial taxa and bacterial pathways. Phenome-wide association studies (PheWAS) were performed on predicted high-impact variants. Additionally, we compared methodological approaches to assess their impact on microbiome composition and reproducibility.ResultsWe identified significant associations between host genetic variants and the relative abundance of one bacterial family, one genus, one species and eight bacterial pathways (p ≤ 5×10−8). However, none of these associations surpassed the stringent significance threshold of p ≤ 2.75×10−11. Notably, we were unable to replicate associations reported in prior studies, including those conducted in Japanese populations, even regarding the direction of effects. Our PheWAS analysis uncovered a frameshift variant in the OR6C1 gene (rs5798345-CA) that was significantly associated with an increased abundance of Bacteroides uniformis. Furthermore, comparative analyses highlighted that methodological differences, particularly in sample processing and DNA extraction protocols, substantially influence the observed gut microbiome composition. This variability may be a key factor contributing to the lack of reproducibility across studies.ConclusionOur findings enhance the understanding of how host genetics shape the gut microbiota in the Japanese population and underscore the importance of methodological standardization in microbiome research. The identified associations between host genetic variants and specific microbial taxa provide insights into the complex interplay between genetics and the gut microbiome. Addressing methodological discrepancies is crucial for improving reproducibility and advancing knowledge of host–microbiome interactions.